Study on the Sympthom of Tendinopathy of Achilles Tendon in Athletics - Ratko Pavlovic (Current Approaches in Science and Technology Research Vol. 7, 2021)
The “Tendinitis of Achilles tendon” (TAT) or "Achilles tendon ruptures" (ATR) symptom is a very delicate problem which needs to be solved as soon as the first symptoms appear. It is necessary to conduct a correct anamnesis of the problem, to determine the diagnosis and method of treatment, as well as the introduction of controlled exercises that can contribute to a faster recovery so that the sportsman, an athlete can bring their body to its form and continue training and competition. Athletes often develop inflammation of tendons called tendinitis. This disease can affect only the tendon or tendon wrap or both at the same time. In the case of isolated inflammation of the tendon wrap, what hap-pens is swelling and thickening, which makes sliding (moving) of the tendon within its shell difficult, causing creaking or cracking (crepitation). The most common locus of inflammation of the tendon is on the back side of the lower half of the forearm and lower leg. Tendinopathy of Achilles tendon predominantly occurs in the jumpers (long jump, triple jump), javelin throwers, runners on tracks from 200m to 1500m and long-distance runners.